Lean Management Technique for Increased Culture Fisheries at Eriwe Cluster Cooperative Fish Farm Estate, Ijebu-Ode, Nigeria - Sule, Shakiru Okanlawon; Oyebola, Oyediran Olusegun; Olaifa, Flora E.; Omitoyin, S. A; Oduntan, O. B; Ewutanure, Jacob Somorhire; Eriegha, Ochuko Joshua; Okitikpi, Tuoyo Diamond; Uchendu, T. E; Adeniyi, M. A; Akuwa, E.; Lawrence, T; et al. (TBTI Global Book Series, 2025)
There has been an increase in aquaculture production of catfish in Nigeria, making the country the highest catfish producer in Africa. The value chain of this fishery has been immensely impacted upon, and has served in sustainable livelihood for fish farmers. Cluster cooperative fish farm estate also improved production through economies of scale. The management techniques being used by the cluster cooperative fish farmers have been built through experience and resilience to the various challenges encountered on production system. The Lean Management Technique was used to identify various challenges encountered on Eriwe Cluster Cooperative Fish Farm through the training of Lean Subject Management Experts and by looking at how the effects of these challenges can be minimized to achieve profitable production from catfish culture. Lean Subject Management Experts were selected from cluster cooperative fish farms in Ogun State and Delta State and were trained at various stakeholders’ meetings, either virtually, in class on during field trips with the assistance of WorldFish/Fish Innovation Lab/USAID and University of Ibadan.